2017
DOI: 10.21082/bullittro.v28n1.2017.1-14
|View full text |Cite
|
Sign up to set email alerts
|

Penyebaran Benih Varietas Unggul Jambu Mete Di Kawasan Timur Dan Barat Indonesia

Abstract: <p>Rehabilitasi dan ekstensifikasi pertanaman jambu mete di sentra produksi merupakan program strategis untuk meningkatkan produksi nasional. Menteri Pertanian sudah melepas sembilan varietas unggul jambu mete nasional. Dalam pelaksanaannya, program rehabilitasi dan ekstensifikasi masih terkendala oleh terbatasnya jumlah benih unggul karena sistem penyebarannya masih belum tertata secara baik. Tujuan penelitian adalah mengidentifikasi dan mengevaluasi penyebaran benih varietas unggul jambu mete di sentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…It is known that GAL 2 is a high yielding kencur variety that is very responsive and more stable to differences in its growing environment. Kencur GAL 2 is also specifically adapted to the growing environment at an altitude of 350-650 m asl with an essential oil content of 2.1-6.6% (Rostiana et al 2006;Rostiana and Effendi, 2007). PBG: Purbalingga, CLP: Cilacap, PWJ: Purworejo, KRA: Karanganyar, PCT: Pacitan, MAD: Madiun, GAL1: Galesia 1, GAL2: Galesia 2, and GAL3: Galesia 3.…”
Section: Extract Of Kencur Rhizomementioning
confidence: 99%
See 2 more Smart Citations
“…It is known that GAL 2 is a high yielding kencur variety that is very responsive and more stable to differences in its growing environment. Kencur GAL 2 is also specifically adapted to the growing environment at an altitude of 350-650 m asl with an essential oil content of 2.1-6.6% (Rostiana et al 2006;Rostiana and Effendi, 2007). PBG: Purbalingga, CLP: Cilacap, PWJ: Purworejo, KRA: Karanganyar, PCT: Pacitan, MAD: Madiun, GAL1: Galesia 1, GAL2: Galesia 2, and GAL3: Galesia 3.…”
Section: Extract Of Kencur Rhizomementioning
confidence: 99%
“…The quality of kencur is determined by the content of essential oils with the main component ethyl-p-methoxy cinnamate (EPMS), which is a secondary metabolite derived from cinnamic acid from the phenol group which is responsible for the distinctive aroma and taste of kencur (Tripathi et al 2013). Research on the effect of altitude on the secondary metabolite content of kencur has been reported by Roemantyo and Somaatmadja (1996), Yusron and Januwati (2003), Rostiana and Effendi (2007), Rostiana et al (2009), and Rostiana and Subaryanti (2010). However, research on the total phenolic content of several accessions of kencur from Purbalingga (PBG), Cilacap (CLP), Purworejo (PWJ), Karanganyar (KRA), Pacitan (PCT), and Madiun (MAD) at several altitudes has not been carried out.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, there is no detailed information about the characteristics of growth and yield due to the lack of research on cashew in Baubau City, Southeast Sulawesi. Rostiana et al (2017) reported the rare research in distinguishing the quantity and quality of yield between yellow and red pseudo-fruits. On the other hand, the information of growth characteristics and yield are able to be used as a reference for the planting management in optimizing the productivity of cashew plantation such as fertilization, pruning, rejuvenation, and cultivating of the plant material.…”
Section: Introductionmentioning
confidence: 99%
“…Higher yields plant is usually supported by an optimum photosynthetic rate. Rostiana et al (2017) reported that the most cultivated varieties of cashew plant in Indonesia were the varieties with the red and yellow color in pseudo-fruit. Both of cashew cultivars could be distinguished from the color of their pseudo-fruit.…”
Section: Introductionmentioning
confidence: 99%